SVC-A2C - Actor Critic Algorithm to Improve Smart Vacuum Cleaner - Aleixo, Everton; Colonna, Juan; Barreto, Raimundo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
This work present a new approach to develop a vacuum cleaner. This use actor-critic algorithm. We execute tests with three other algoritms to compare. Even that, we develop a new simulator based on Gym to execute the tests.